The Dynamic Effects of Social Accountability Initiatives in Governance for the South African Public Service Sector - Enaifoghe, Andrew (International Journal of Business, Economics, and Social Development, 2024)
The objective of the study explore the idea of social accountability in governance, paying close attention to the interactions and synergies between information, citizen participation, and governmental responsiveness. In earlier research, scholars frequently made the implicit assumption that information paved the way for citizens' voices and, in turn, state responsiveness. Enhanced public action is a requisite, but not an adequate, precondition for social accountability in governance. Furthermore, a positive state response does not always follow the citizen's voices. Service providers and officials may choose to ignore the voice of the citizen, respond to it with retaliation, or, despite good intentions, be limited in their ability to respond due to a lack of capacity or resources. The study indicated that more effective than initiatives that only encourage localized change, strategic actions include a focus on creating an enabling environment and enhancing governmental responsiveness. Findings show that a positive governmental response may not always result from a citizen's voice, despite good intentions, service providers and officials may choose to ignore or respond to public complaints with harsh measures, or they may simply not have the means or capacity to do so. The study concluded that more effective than initiatives that solely support localized citizen voice, strategic actions involve a focus on creating an enabling environment and enhancing governmental responsiveness.Keywords: Social accountability, governance, initiatives, responsiveness, citizens, interactions